İlkokul Öğrencilerinin Empresyonizme Yönelik Görüşlerinin Görsel Okuryazarlık Bağlamında İncelenmesi - Hiçyilmaz, Yahya (Muş Alparslan Üniversitesi, 2020)
The aim of this study is to examine the views of the elementary school students towards Impressionism art movement in the context of visual literacy. The research was conducted with a descriptive approach in terms of purpose and method. The study group of the study was formed with 526 students. In order to determine the data collection tools, a landscape painting belonging to three periods of Impressionism art movement was chosen according to the opinions of three visual arts experts. Then, the collected data were analysed in terms of content analysis and descriptive statistics. According to the results of the study, it was determined that the students were more interested in the works of the last period of Impressionism art movement. It was seen that the paintings which the students were interested in were those based on the subject matter of the work. In addition, it was determined that the students have more explanations about visual literacy of the works belonging to the last period of Impressionism art movement. In the research, based on the results obtained, it is recommended to create environments where primary school students can express their thoughts for different works of art within the framework of visual literacy.

Bu araştırmanın amacı, ilkokul döneminde öğrenim gören öğrencilerin empresyonizm sanat akımına yönelik görüşlerini görsel okuryazarlık bağlamında incelemektir. Araştırma, amaç ve yöntem açısından betimleyici bir yaklaşım izlenerek yürütülmüştür. Araştırmanın çalışma grubu, 526 öğrenci ile oluşturulmuştur. Veri toplama araçlarını belirlemek amacıyla Empresyonizm sanat akımının üç dönemine ait birer manzara resmi, üç görsel sanatlar uzmanın görüşleri doğrultusunda seçilmiştir. Veriler, içerik analizi ve tanımlayıcı istatistik teknikleri ile analiz edilmiştir. Araştırmanın sonucunda, öğrencilerin Empresyonizm sanat akımının son dönemine ait eserlere daha çok ilgi duydukları bulunmuştur. Öğrencilerin ilgi duydukları tabloları, daha çok eserin konusunu temel alarak seçtikleri görülmüştür. Ayrıca öğrencilerin Empresyonizm sanat akımının son dönemine ait eserlerinin görsel okur ve görsel yazarlık unsurlarına yönelik açıklamalarının daha fazla olduğu belirlenmiştir. Çalışmada, elde edilen sonuçlardan hareketle ilkokul öğrencilerinin farklı sanat eserlerine yönelik görsel okuryazarlık çerçevesinde düşüncelerini ifade edebileceği ortamların oluşturulması önerilmektedir.
Reviewing of Primary School Students’ Views on Impresionism in the Context of Visual Literacy
anemon
Keywords: Visual literacy; Impressionism; Students; Görsel okuryazarlık; Empresyonizm; Öğrenciler